Assessing the role of managerial feedback in changing routines in small and medium enterprises. Issue 3 (26th February 2021) - Blakçori, Feim; Aroles, Jeremy
Abstract : Purpose: In an ever-complexifying business context, organizations need to continuously adapt, adjust and change their routines in order to remain competitive. Drawing upon a qualitative study focusing on three Southeastern European countries (Greece, Bulgaria and Serbia), this paper explores the role played by managerial feedback on routine change within small and medium enterprises (SMEs). Design/methodology/approach: The authors draw from an in-depth qualitative study of six manufacturing SMEs located in three Southeastern European countries: Greece, Bulgaria and Serbia. The process of data collection, which spanned over a period of fifteen months, was centred around both interviews and observations. Findings: The authors argue that feedback is a powerful and constructive managerial practice that sets to initiate changes in routines through three different means: (1) making sense of the changes required (by channelling information), (2) rationalizing the decision for changing the unproductive routines and (3) reviewing the process of change through the legitimization of situational routines. In addition to this, the authors found that managers perceive that routines need to change for four main reasons: inability to meet targets (e.g. performance); too cumbersome to deal with complex environments; inflexibility and failing to provide control; obsolete in terms of providing a sense of confidence. Practical implications: This research provides evidence that feedback is an important managerial means of changing routines in informal, less bureaucratic and less formalized workplaces such as SMEs. Managers might embrace deformalized approaches to feedback when dealing with routines in SMEs. Working within a very sensitive structure where the majority of changes on routines need to be operationalized through their hands, managers and practitioners should deploy feedback in order to highlight the importance of routines as sources of guiding actions, activities and operations occurring in SMEs that create better internal challenges and processes. Originality/value: The authors' research suggests that routines are subject of change in dynamic and turbulent situations. Perceiving routines as antithetical to change fails to capture the distinctive features of change such as its fluidity, open-endedness, and inseparability. Likewise, the authors claim that routines are socially constructed organizational phenomena that can be modulated in different ways in SMEs.